The Placing of Early Bronze Age Metalwork Deposits: New Evidence from Scotland. Issue 2 (1st February 2018) - Bradley, Richard; Green, Chris; Watson, Aaron
Summary: This paper considers the earliest metalwork hoards in Scotland, most of which have been found at conspicuous points in the landscape. The treatment of individual objects suggests that they had been carefully selected before they were deposited. Fieldwork, combined with computer reconstruction, shows that half the collections with adequate provenances come from places with direct views of the rising and setting sun at the solstices. The main emphasis seems to have been on midwinter.